Innovation and Entrepreneurship Strategies of Teachers and Students in Financial Colleges and Universities Under the Direction of Food Security - Haojie, Guan (Frontiers in Psychology, 2022)
This study aims to better promote the innovation and entrepreneurship of teachers and students in finance and economics colleges and universities in terms of food security. Based on the relevant theories such as food security, innovation and entrepreneurship, the questionnaire was used to investigate the issues related to food security of teachers and students in colleges and universities. Next, the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) analysis method was introduced to evaluate the safety metrics of the response subsystem. Finally, Internet of Things (IoT) monitoring technology was applied to grain growth and sales. The research results show that college teachers and students have a disjointed cognition of food security as important talents in innovation and entrepreneurship. After the TOPSIS analysis method is used to study, when college teachers and students choose to start a business in food security, they must pay attention to the changes in economic factors. The IoT monitoring technology is applied to grain growth and sales, and the monitoring technology of the IoT could reduce the mortality rate of corn seedlings to 3.59%. The mortality rate of seedlings is much higher than that of farmers relying on their own experience to grow corn. Therefore, this has great reference significance for the innovation and entrepreneurship development of college teachers and students in food security at this stage.